Recognizing Leisure: A Portrait of the Concept through the Educated Self - Ildefonso-Sánchez, Givanni (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
Much of the current available literature on leisure characterizes it as an additional consumer good: a derivative of capitalist society, featured as a commodity and, for the most part, an industry. This paper argues that recovering the concept of leisure from the ancients, with a contemporary focus on culture and the practice of living artfully, will help us create a new understanding of leisure that will break free from the reigning popular focus on “free time.” The concept of leisure (scholé) will here be set against an existential backdrop that will situate it entirely within the realm of education, to reveal important connections to what it means to be an educated self and to lead a flourishing collective life in the form of culture. This discussion will conclude with a portrait of the concept that will be of interest to democracy-oriented educators, as we set the groundwork for actualizing the concept in the practice and lives of teachers and students in today’s world.